Kajian Pelaksanaan Pendampingan Serta Pemeriksaan Pengelolaan Keuangan SMA/SMK Negeri Oleh Auditor Inspektorat Daerah Guna Meminimalisir Penyimpangan Pengelolaan Keuangan - Pakasi, Novrabella Clarashinta (Universitas Gorontalo, 2022)
The purpose of research to find out the implementation of mentoring and financial management audits for SMA/SMK Negeri in North Sulawesi Province by regional inspectorate auditors in order to minimize financial management irregularities. This research was conducted at the Provincial Government of North Sulawesi. The data analysis techniques are data reduction, data display and conclusion drawing/verification which are carried out interactively and take place continuously until complete, so that the data reaches saturation. The results of this study indicate that financial management assistance for SMA/SMK by the Regional Inspectorate auditor is sufficient to minimize financial management irregularities. With the assistance of the regional inspectorate auditor, the school gets additional knowledge that can be used in the implementation of school financial management. 2) Examination of SMA/SMK Financial Management by the Regional Inspectorate auditor is sufficient to minimize financial management irregularities. With the examination of SMA/SMK financial management from the regional Inspectorate auditor, the school gets suggestions for improvement that can be used to correct mistakes.